Safe and successful transition from oral selexipag to subcutaneous treprostinil in a patient with idiopathic pulmonary arterial hypertension treated with triple combination therapy. Issue 1 (July 2022) - Adachi, Shiro; Nishiyama, Itsumure; Yasuda, Kenichiro; Yoshida, Masahiro; Nakano, Yoshihisa; Kondo, Takahisa; Murohara, Toyoaki
Abstract: Some patients with pulmonary arterial hypertension (PAH) might undergo transition to parenteral prostacyclin analogs due to inadequate response to oral combination therapy. However, there is no consensus on how transition from oral selexipag to subcutaneous treprostinil should be performed. Herein, we report a 56-year-old woman diagnosed with idiopathic PAH that was treated with initial combination therapy (10 mg of macitentan, 40 mg of tadalafil, and 3.2 mg of selexipag daily). Mean pulmonary arterial pressure (PAP) improved from 63 to 39 mm Hg. Transition to parenteral prostacyclin analog was required because cardiac index was below 2.5 L/min/m 2 . The selexipag was tapered off while subcutaneous treprostinil was titrated up to 30 ng/kg/min over 19 days. Hemodynamic parameters were slightly better than those before the transition. The mean PAP improved to 32 mm Hg by further gradual increases of subcutaneous treprostinil up to 60 ng/kg/min. Therefore, the patient having idiopathic PAH with inadequate response to oral triple combination therapy experienced successful transition from selexipag to subcutaneous treprostinil. Hemodynamic parameters were slightly more improved at a dose of 30 ng/kg/min of subcutaneous treprostinil than at a dose of 3200 μg daily of selexipag in the midst of disease progression. Learning objectives: There is limited evidence for transition of pulmonary vasodilators, especially from oral selexipag to subcutaneous treprostinil. Detailed change in hemodynamic parameters before and after transition and the way of performing transition in patients with idiopathic pulmonary arterial hypertension with exacerbations despite treatment with oral triple combination therapy may provide useful information for better management in the clinical setting.